Assessment of impact of country business ranking on economic development: An empirical analysis - Mohd Naved Khan (Global Business & Finance Review (GBFR), 2024)
Purpose: The World Bank's "Ease of Doing Business" index, among other business rankings, can help a country's economic progress by attracting foreign investments, encouraging entrepreneurship, and improving the business climate. Superior rankings indicate an optimised environment for business activities, which could boost investments, job opportunities, and overall economic growth. The research is conducted to assess the impact of a country's business ranking on economic development. Design/methodology/approach: The Structural Equation Modelling (SEM) method was used to assess the impact of a country's business ranking on its economic trajectory. The official World Bank report was used to obtain data from 2015 to 2021. Panel data of Global Innovation Ranking, Ease of Doing Business Ranking, and Business Freedom Ranking from 2016 to 2021 is the basis of this study. The researcher has used a conceptual framework to establish and understand the dependence among the dependent and independent variables. For measuring statistical association, the researcher has used structural equation modelling and path diagram along with correlation and regression analysis. The correlation has been used to assess their association, while the researcher has used regression to determine the impact of country business ranking. Findings: The investigator investigated the impact of India's standings in the Global Innovation Ranking, Ease of Doing Business Ranking, and Business Freedom Ranking on its Economic Development, specifically GDP, in this study. The study's findings show that India's business rankings have a significant impact on its economic development. Such global business rankings provide critical data points for policymakers, businesses, and investors to make informed decisions, thereby promoting economic growth. Furthermore, the study examined the effects of GDP growth on the combustion of fossil fuels, as measured in million tonnes, emphasising the environmental consequences of economic expansion. Research limitations/implications: It's imperative to note that this is just an estimate, and the actual relationship between the variables in the population may differ from this estimate. The estimate is based on the sample data used to fit the model and may not accurately reflect the true relationship in the population. Further analysis and interpretation of the model's goodness of fit and consideration of other factors, such as outliers or omitted variables, are essential to fully apprehend the relationship between "GIR" and the dependent variable. The results of global business rankings can help policymakers identify areas for improvement in their country's business environment. By focusing on the areas where their country is lagging behind, they can develop policies and initiatives to attract more investment, create a more favourable business environment, and support economic growth. Businesses can use the results of global rankings to evaluate potential locations for expansion or investment. It can provide insights into the ease of starting and running a business, access to credit, property rights protection, and other important factors to businesses. Investors can also use the results of global rankings to make informed decisions about where increased investment and economic growth. Global business rankings generally provide valuable information that policymakers, businesses, and investors can use to make informed decisions and support economic development. Originality/value: I hereby attest that the research paper I have submitted is the result of my own independent and unique labor. All of the sources from which the thoughts and passages were derived have been properly credited. The work has not been submitted for publication anywhere and is devoid of any instances of plagiarism.
Keywords: 650; Global innovation ranking; Ease of doing business ranking; Business freedom ranking; GDP growth; Environment degradation